1994
DOI: 10.1177/154193129403800108
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of +Gz on Cognitive Performance

Abstract: A study is described which examines the interaction of two of the most salient stressors found in the tactical aviation cockpit: 1) highly demanding decision-making tasks, and 2) intermittent periods of high G. Addressing this issue is critical because: 1) it is probable that physiological stressors such as G may have serious ramifications on pilots' abilities to perform complex cognitive tasks; 2) there may be different impacts of G on different types of cognitive tasks, and the impact of these deficits may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These effects are summarized in Figure 3. It is important to note that the degraded performance interval observed in this study represents but one set of conditions and that the interval may possibly vary as a function of several other factors, such as dynamic changes in the onset profile that a pilot might endure (Houghton et al, 1985;Morrison, et al, 1994) or the use of anti-G protection.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are summarized in Figure 3. It is important to note that the degraded performance interval observed in this study represents but one set of conditions and that the interval may possibly vary as a function of several other factors, such as dynamic changes in the onset profile that a pilot might endure (Houghton et al, 1985;Morrison, et al, 1994) or the use of anti-G protection.…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings corroborate the impact of ±Gz acceleration on task performance documented in prior research. For example, an experimental study investigating the effects of ±Gz acceleration on cognitive performance showed performance degradation across individuals on a compensatory tracking task, a system monitoring task, and a strategic resource management task [29]. The results of our study suggests that field dependent individuals would benefit from mobile displays that provide support for disambiguation of objects and artifacts in a perceptual field.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, little is known regarding interaction effects between extreme environments' physical stressors and human cognitive abilities [31]. Even less is known regarding interaction effects between field dependency independency as a perceptual style and ±Gz accelerations as an extreme environment physical stressor [29,39]. Acknowledging these gaps in our understanding of this dynamic interdependence of variables and integrating lines of empirical research in cognitive psychology and human physiology, the experimental study reported here investigates how performance varies between field dependent and field independent groups under conditions of alternating ±Gz accelerations.…”
Section: Performance Degradation In Altered Gz Environmentsmentioning
confidence: 99%
“…+Gz can cause a reduction in the pilot's brain blood pressure, and it takes a certain amount of time until the body can compensate for this change. A study investigated the effects of ±Gz acceleration on cognitive performance revealed performance degradation in tracing, system monitoring and a strategic resource management task [14]. Another limitation worth mentioning are the physical conditions of participants.…”
Section: Discussionmentioning
confidence: 99%